PENYULUHAN TEKNOLOGI DALAM KEHIDUPAN RUMAH TANGGA - Nia Ekawati; Shandy Tresnawati; Novita Lestari Anggreini; Ayu Hendrati Rahayu (PUAN INDONESIA, 2023)
Humans express technology starting from their intellect and mind. With this, humans have a desire to get out of trouble, wanting to live better, more comfortable and safer. Productive counselling that we do to residents of Taman Bukit Cibogo RT. 08 RW. 17 Leuwigajah Cimahi Selatan regarding technology counselling in household life. The purpose of this service is to convey to residents about applications that can be used in everyday life to help activities carried out by each of them. The application used is on average a digital application that we can download on the playstore or Appstore platform. Based on the results of the service carried out on residents of Taman Bukit Cibogo RT. 08 RW. 17 Leuwigajah Cimahi Selatan, they were quite enthusiastic about the application that the service team conveyed, some even asked for help to install the application they wanted.